Facile synthesis of novel porous self-assembling hydrogen-bonding covalent organic polymers and their applications towards fluoroquinolone antibiotics adsorption. Issue 58 (1st October 2018) - Li, Zhuoran; Xu, Feifan; Liu, Zhi; Qin, Chuanyu; Ren, Hao; Li, Yangxue
Abstract : A series of porous hydrogen-bonding covalent organic polymers (HC OPs) have been synthesized based on three-composite building blocks through a quick and succinct method for fluoroquinolone antibiotics adsorption from aqueous solutions. Abstract : A series of porous hydrogen-bonding covalent organic polymers (HC OPs) have been synthesized based on three-composite building blocks through a quick and succinct method for fluoroquinolone antibiotics adsorption from aqueous solutions. The porous properties of the HC OPs were regulated and controlled by adjusting the lengths of linkers, and the crystallinity and stability were strengthened due to the introduction of hydrogen bonds in HC OPs. Taking advantage of the porous properties and π-conjugated phenyl rings, as well as functional –CO–NH– and –COOH groups, HC OPs removed organic pollutants from wastewater effectively and showed good reusability. The external adsorption behavior was analyzed using both kinetic analysis and isotherm analysis. The results showed that the adsorption obeys the pseudo-second order kinetic model and follows the Langmuir isotherm model. The obtained maximum adsorption capacity of the four HC OPs was arranged in sequence according to the specific surface areas and pore sizes. Furthermore, the internal mechanisms involving perforated porousness, electrostatic interaction, hydrophobic interaction, π–π electron-donor–acceptor (EDA) interaction and hydrogen bonding formation, were investigated in detail. We envisage broadly applying the HC OPs in the facile and effective management of environmental pollution.